2001
DOI: 10.1007/s11661-001-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Strength and conductivity of Cu-9Fe-1.2X (X = Ag or Cr) filamentary microcomposite wires

Abstract: In this study, strength and electrical conductivity of Cu-9Fe-1.2X (X ϭ Ag or Cr) microcomposite wires obtained by cold drawing combined with intermediate heat treatments have been investigated. During cold working, the primary and secondary dendrite arms are aligned along the drawing direction and elongated into filaments. The addition of Ag was found to reduce the filament spacings at the given draw ratio throughout the drawing processing. The ultimate tensile strength and the conductivity of the Cu-Fe-Ag mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…[1±10] The scale of the final microstructure is determined by the cold-working strain and the initial dendrite size. [2,4,8] In Table 1, the strength and conductivity of Cu±Fe microcomposites reported in the literature are summarized. Initial Cu±Fe billets can be fabricated by either casting [8,11,13,15] or powder processing.…”
Section: Development Of Microstructure and Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[1±10] The scale of the final microstructure is determined by the cold-working strain and the initial dendrite size. [2,4,8] In Table 1, the strength and conductivity of Cu±Fe microcomposites reported in the literature are summarized. Initial Cu±Fe billets can be fabricated by either casting [8,11,13,15] or powder processing.…”
Section: Development Of Microstructure and Propertiesmentioning
confidence: 99%
“…[2,4,8] In Table 1, the strength and conductivity of Cu±Fe microcomposites reported in the literature are summarized. Initial Cu±Fe billets can be fabricated by either casting [8,11,13,15] or powder processing. [2,9,10,12] The size of the dendrites will depend on the solidification rate and the nature of the solid/liquid reaction.…”
Section: Development Of Microstructure and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has reported that a third alloying element can refine the microstructure and enhance the properties of Cu-based composites. Song et al 14,15) reported that the 0.1 mass% Ag refined the primary Fe dendrites in the as-cast microstructure of Cu9 mass%Fe. Gao et al 16,17) reported that Cu11Fe 6Ag (mass%) in situ composites had higher tensile strength and conductivity (1020 MPa/70.5%IACS, respectively) at strain of 10 compared to Cu12Fe.…”
Section: Introductionmentioning
confidence: 99%